The Influence of Organizational Culture on Organizational Citizenship Behavior with The Mediation Role of Organizational Commitment at The Housing Provision Implementation Center Office of Maluku Province - Semuel Souhoka (West Science Social and Humanities Studies, 2026)
This study aims to analyze the influence of organizational culture on Organizational Citizenship Behavior (OCB) with the mediating role of organizational commitment at the Maluku Province Housing Provision Implementation Office. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The population in this study was all 51 employees, with the sampling technique using saturated sampling. The results of the study indicate that organizational culture has a positive and significant effect on organizational commitment and OCB. Organizational commitment also has a positive and significant effect on OCB. In addition, organizational commitment is proven to play a significant role as a mediating variable in the relationship between organizational culture and OCB. This indicates that a strong organizational culture can increase employee engagement, which ultimately encourages extra-role behavior (OCB). This study implies that strengthening organizational culture and increasing employee commitment are important factors in encouraging positive work behavior and increasing organizational effectiveness.